Runtime Aware Architectures; Barcelona Supercomputing Center at a glance - Valero, Mateo (My University, 2015)
In the last few years, the traditional ways to keep the increase of hardware performance to the rate predicted by the Moore's Law have vanished. When uni-cores were the norm, hardware design was decoupled from the software stack thanks to a well defined Instruction Set Architecture (ISA). This simple interface allowed developing applications without worrying too much about the underlying hardware, while hardware designers were able to aggressively exploit instruction-level parallelism (ILP) in superscalar processors. With the irruption of multi-cores and parallel applications, this simple interface started to leak. As a consequence, the role of decoupling again applications from the hardware was moved to the runtime system. Efficiently using the underlying hardware from this runtime without exposing its complexities to the application has been the target of very active and prolific research in the last years. Current multi-cores are designed as simple symmetric multiprocessors (SMP) on a chip. However, we believe that this is not enough to overcome all the problems that multi-cores already have to face. It is our position that the runtime has to drive the design of future multi-cores to overcome the restrictions in terms of power, memory, programmability and resilience that multi-cores have. In this talk, we introduce a first approach towards a Runtime-Aware Architecture (RAA), a massively parallel architecture designed from the runtime's perspective. The BSC is the Spanish national supercomputing lab and does research into Computer, Life, Earth and Engineering Sciences. BSC provides supercomputing services to Spanish and European scientists and generates knowledge and technology to transfer to business and society. BSC is a Severo Ochoa Centre of Excellence and has a long record of carrying our excellent research through competitively funded projects, particularly in Europe and with industry. BSC works with the most important IT companies and with many others in different application areas, particularly energy and medicine. BSC tries to promote collaboration between Europe and Latin America and is committed to education and training in the field of HPC.
Keywords: Programación en paralelo (Informática); Parallel architectures; Parallel programming